2016
DOI: 10.9745/ghsp-d-15-00197
|View full text |Cite
|
Sign up to set email alerts
|

Role of Social Support in Improving Infant Feeding Practices in Western Kenya: A Quasi-Experimental Study

Abstract: Fathers and grandmothers who participated in separate nutrition dialogue groups supported mothers to improve infant feeding practices including dietary diversity, food consistency, and use of animal-source foods. Future studies should explore using a family-centered approach that engages mothers together with key household influencers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
129
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(151 citation statements)
references
References 38 publications
(47 reference statements)
20
129
0
2
Order By: Relevance
“…The outcomes of this study were similar to those reported in an intervention in Western Kenya that aimed at providing social support to the mother by enlisting fathers and grandmothers in encouraging specific practices for infant feeding. Significant improvements were reported for minimum meal frequency (OR 1.14, 95% CI:1.00–1.30, p  = 0.047) and minimum dietary diversity (OR 1.19, 95%CI:1.01–1.40, p  = 0.04) [22]. …”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of this study were similar to those reported in an intervention in Western Kenya that aimed at providing social support to the mother by enlisting fathers and grandmothers in encouraging specific practices for infant feeding. Significant improvements were reported for minimum meal frequency (OR 1.14, 95% CI:1.00–1.30, p  = 0.047) and minimum dietary diversity (OR 1.19, 95%CI:1.01–1.40, p  = 0.04) [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Our findings underscore the importance of women's social support for promoting the adoption of healthy IYCF practices, with significant positive associations for each of the IYCF indicators assessed and is consistent with a growing literature examines various dimensions of maternal well‐being with IYCF and nutritional status. Social support has been demonstrated to be associated with improved breastfeeding and complementary feeding (Bosire et al, ; Mukuria, Martin, Egondi, Bingham, & Thuita, ), and a review of women's empowerment and child nutritional status in South Asia concluded that social support is a relatively understudied construct in relation to nutritional status (Cunningham, Reul, et al, ). Social support can create an enabled environment for child feeding and access to knowledge and skills for child feeding but may also complicate women's feeding abilities through trade‐offs in workload and time for childcare (Cunningham, Ruel, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that if facility‐ and community‐based health workers and volunteers provide more information and support to mothers and other family members during the antenatal and post‐natal periods, support for EBF may increase. Our data also showed that mothers were not receiving the desired Emotional or Instrumental support that suggests the need for interventions to increase support for recommended infant feeding practices (Alive & Thrive, ; Aubel, ; Flax et al, ; Mukuria, Martin, Egondi, Bingham, & Thuita, ). Programmatically, when administered before delivery, the scale could help to identify mothers who may have challenges with EBF.…”
Section: Discussionmentioning
confidence: 61%